The Integration of Hydrogen Energy Storage (HES) in Germany: What Are the Benefits for Power Grids? - Mirza Sarajlić; Dorothee Peters; Mahdi Takach; Frank Schuldt; Karsten von Maydell (Energies)
This article provides an overview of the requirements for a grid-oriented integration of hydrogen energy storage (HES) and components into the power grid. Considering the general definition of HES and the possible components, this paper presents future hydrogen demand, electrolysis performance, and storage capacity. These parameters were determined through various overall system studies aiming for climate neutrality by the year 2045. In Germany, the targeted expansion of renewable energy generation capacity necessitates grid expansion to transport electricity from north to south and due to existing grid congestions. Therefore, electrolysis systems could be used to improve the integration of renewable energy systems, by reducing energy curtailment and providing grid services when needed. Currently, however, there are hardly any incentives for a grid-friendly allocation and operation of electrolysis or power-to-gas plants. Two possible locations for hydrogen plants from two current research projects HyCavMobil (Hydrogen Cavern for Mobility) and H2-ReNoWe (Hydrogen Region of north-western Lower Saxony) are presented as practical examples. Using power grid models, the integration of electrolysis systems at these locations in the current high and extra-high voltage grid is examined. The presented results of load flow calculations assess power line utilization and sensitivity for different case scenarios. Firstly, the results show that power lines in these locations will not be overloaded, which would mean an uncritical operation of the power grid. While the overall grid stability remains unaffected in this case, selecting suitable locations is vital to prevent negative effects on the local grid.